The regulation of public service broadcasters: Should there be more advertising on television? - Gregory S. Crawford; Lachlan Deer; Jeremy Smith; Paul Sturgeon (University of Zurich, Department of Economics, 2017)
Increased competition for viewers' time is threatening the viability of public-service broadcasters (PSBs) around the world. Changing regulations regarding advertising minutes might increase revenues, but little is known about the structure of advertising demand. To address this problem, we collect a unique dataset on monthly impacts (quantities) and prices of UK television channels between 2002 and 2009 to estimate the (inverse) demand for advertising on both public and commercial broadcasters. We find that increasing PSB advertising minutes to the level permitted for non-PSBs would increase PSB and industry revenue by 10.5% and 6.7%.
Keywords: D2; L1; L5; M3; 330; Advertising; public service broadcasting; television markets; inverse demand